New endophytic strains of Trichoderma promote growth and reduce clubroot severity of rapeseed (Brassica napus) - Hasan, Mahmodol; Hossain, Motaher; Jiang, Daohong (PloS one, 2023)
Rapeseed ( Brassica napus L.) is the world’s third most important edible oilseed crop after soybean and palm. The clubroot disease caused by Plasmodiophora brassicae poses a significant risk and causes substantial yield losses in rapeseed. In this study, 13 endophytic fungal strains were isolated from the healthy roots of rapeseed ( B . napus ) grown in a clubroot-infested field and molecularly identified. Based on germination inhibition of resting spores of P . brassicae , two endophytic fungal antagonists, Trichoderma spp. ReTk1 and ReTv2 were selected to evaluate their potential for plant growth promotion and biocontrol of P . brassicae . The Trichoderma isolates were applied as a soil drench (1×10 7 spore/g soil) to a planting mix and field soil, in which plants were grown under non-infested and P . brassicae -infested (2×10 6 spore/g soil) conditions. The endophytic fungi were able to promote plant growth, significantly increasing shoot and root length, leaf diameter, and biomass production (shoots and root weight) both in the absence or presence of P . brassicae . The single and dual treatments with the endophytes were equally effective in significantly decreasing the root-hair infection, root index, and clubroot severity index. Both ReTk1 and ReTv2 inhibited the germination of resting spores of P . brassicae in root exudates. Moreover, the endophytic fungi colonized the roots of rapeseed extensively and possibly induced host resistance by up-regulated expression of defense-related genes involved in jasmonate ( BnOPR2 ), ethylene ( BnACO and BnSAM3 ), phenylpropanoid ( BnOPCL and BnCCR ), auxin ( BnAAO1 ) and salicylic acid ( BnPR2 ) pathways. Based on these findings, it is evident that the rapeseed root endophytes Trichoderma spp. ReTk1 and ReTv2 could suppress the gall formation on rapeseed roots via antibiosis, induced systemic resistance (ISR), and/or systemic acquired resistance (SAR). According to our knowledge, this is the first report of the endophytic Trichoderma spp. isolated from root tissues of healthy rapeseed plants ( B . napus .), promoting plant growth and reducing clubroot severity.